1999
DOI: 10.1007/s002340050848
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the degree of contrast enhancement and the volume of peritumoral edema in meningiomas and malignant gliomas

Abstract: Peritumoral edema and contrast enhancement of brain tumors are both thought to be due to breakdown of the blood-brain barrier (BBB); however, the exact mechanism by which these two phenomena occur and whether there is a quantitative or etiological relationship is not known. Our purpose was to determine whether the relationship between the breakdown of the BBB, defined radiologically as the degree of contrast enhancement, and the volume of surrounding edema is different for high-grade gliomas and meningiomas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…A correlation between contrast enhancement and peritumoral edema, indicating similar mechanisms, namely breakdown of the blood-brain barrier for both phenomena, could be established for glioma but not for meningioma [27]. A physical barrier in certain meningiomas might limit propagation of edema into the adjacent white matter.…”
Section: Edema Associated With Tumor Histology and Grade And Therapy-mentioning
confidence: 91%
“…A correlation between contrast enhancement and peritumoral edema, indicating similar mechanisms, namely breakdown of the blood-brain barrier for both phenomena, could be established for glioma but not for meningioma [27]. A physical barrier in certain meningiomas might limit propagation of edema into the adjacent white matter.…”
Section: Edema Associated With Tumor Histology and Grade And Therapy-mentioning
confidence: 91%
“…The explanation may be that BOLD response is inherently a vascular phenomenon, which is marginally affected by tumor size (18,27). However, this should be interpreted with caution, as the exact determination of tumor volumes at routine MR imaging is difficult in gliomas, in which borders are often ill defined (30). The lack of an effect of tumor distance to the PMC may also be supported by the aforementioned studies that demonstrated neurovascular uncoupling past the radiologic borders of the tumors (4,28,31).…”
Section: Neuroradiology: Influence Of Tumor Type and Bold Functional mentioning
confidence: 99%
“…The findings offer indirect radiological evidence that the defect in the BBB which causes edema is etiologically related to the defect in BBB responsible for contrast enhancement 7 . Significant correlation can be found (p=0.0006) between the volume of peritumoural edema and the degree of contrast enhancement in gliomas 8 .…”
Section: Discussionmentioning
confidence: 86%